Small bowel submucosal lipoma-induced secondary intussusception: a case report - Alsulimani, Siraj O.; Aljuhani, Arwa M.; Aljuhani, Ibrahim M.; Alsufyani, Eman Muhsini; Al-Sawat, Abdullah (International Surgery Journal, 2025)
Intestinal lipomas are uncommon and benign tumors that rarely can lead to intussusception in adults. We present a rare case of ileo-ileal intussusception caused by a small intestinal (ileal) lipoma, resulting in intestinal obstruction. A 51-year-old female patient presented to the emergency department with a complaint of abdominal pain persisting for five days, along with nausea and vomiting. A computed tomography (CT) scan revealed an intraluminal soft tissue lesion with a fatty component located in the distal ileum. Emergency laparoscopic exploration confirmed intussusception in the terminal ileum, which was subsequently resected with a 5 cm safety margin on both sides. The resected ileal segment was anastomosed end-to-end. The patient recovered well, and histopathological examination confirmed the diagnosis of an intraluminal intestinal lipoma. In cases of adult intussusception, consideration should be given to the possibility of a small intestinal intraluminal lipoma. Surgical resection is generally recommended for diagnosis and treatment of symptomatic intestinal lipomas.